Endovascular Management of Pediatric Deep Venous Thrombosis - Zavaletta, Vaz; Warren, Beth B.; Katz, Danielle; Eliason, Grace; Collard, Michael; Annam, Aparna (Seminars in Interventional Radiology, 2025)
This study aims to review current practices in thrombolysis and thrombectomy for managing deep venous thrombosis (DVT) and associated complications in the pediatric population. Pediatric thrombosis care has a rich history of evolution, from the early days of anticoagulation to the current era of endovascular therapies. This evolution has been driven by the need for a nuanced, multidisciplinary approach that includes interventional radiology (IR) and hematology. While anticoagulation remains the standard of care, endovascular therapies are increasingly utilized in cases of extensive, occlusive, or limb-threatening DVT, particularly to prevent pulmonary embolism and postthrombotic syndrome (PTS) and to preserve venous patency. This review outlines the indications, contraindications, and procedural techniques for catheter-directed thrombolysis, pharmaco-mechanical thrombectomy (PMT), mechanical thrombectomy, and venous stenting in children. It emphasizes the crucial role of a multidisciplinary team, including pediatric hematologists, interventional radiologists, and other medical professionals, in managing pediatric DVT. This collaboration is essential for considering pediatric-specific factors such as patient size, sedation requirements, radiation, contrast dosing, and anticoagulation. Also highlighted are postprocedural care, anticoagulation strategies, and imaging follow-up. Multidisciplinary collaboration is critical to improving outcomes for children with thrombotic disease.
Keywords: pediatric; DVT; thrombolysis; thrombectomy; anticoagulation